From impossible to inevitable : how hyper-growth companies create predictable revenue - Ross, Aaron, 1971-; Lemkin, Jason, 1969- (John Wiley & Sons, 2016)
Impossible Goals , Inevitable Successes Why are you struggling to grow your business when everyone else seems to be crushing their goals? If you needed to triple revenue within the next three years, would you know exactly how to do it? Doubling the size of your business, tripling it, even growing ten times larger isn't about magic. It's not about privileges, luck, or working harder. There's a template that the world's fastest growing companies follow to achieve and sustain much, much faster growth. From Impossible to Inevitable details the hypergrowth playbook of companies like the record-breaking Zenefits (which skyrocketed from $1 million to $100 million in two years), Salesforce.com (the fastest growing multibillion dollar software company), and EchoSign--aka Adobe Document Services--(which catapulted from $0 to $144 million in seven years). Whether you have a $1 billion or a $100,000 business, you can use the same insights as these notable companies to learn what it really takes to break your own revenue records. For instance, one of the authors shows how he grew his income from $67,000 to $720,000 in four years while maintaining a 20-30 hour work week and welcoming a new child--nine times. This book shows you how to surpass plateaus and get off of the up-and-down revenue rollercoaster by answering three questions about growing revenue to tens times its size: Why aren't you growing faster? What does it take to get to hypergrowth? How do you sustain growth? This powerful, effective book provides a template for you to kick off your biggest growth spurt yet. This template includes The 7 Ingredients Of Hypergrowth: You're not ready to grow until you Nail a Niche . Overnight success is a fairy tale. You're not going to be magically discovered. You need sustainable systems that Create Predictable Pipeline . Growth exposes your weaknesses and it will cause more problems than it solves--until you Make Sales Scalable . It's hard to build a big business out of small deals . Figure out how to Double Your Dealsize . It'll take years longer than you want , but don't quit too soon. Make sure you can Do the Time . Your people are renting, not owning their jobs. Develop a culture of initiative, not adequacy by Embracing Employee Ownership . Employees, you are too accepting of "reality" and too eager to quit. You can Define Your Destiny to make a difference, for yourself and your company, no matter what you do or where you work. The authors take each ingredien...